2012
DOI: 10.1029/2011jb008349
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave tomography of China using joint inversion of body and surface wave constraints

Abstract: The India‐Eurasia collision and the decratonization of the North China Craton have drawn much attention from the scientific community. Here we provide the first large‐scale S wave velocity model for China (CH11‐S) based on constraints from both teleseismic surface and body waves. We take advantage of the recent deployment of the 140 permanent stations of the Chinese Digital Seismic Network and temporary network deployments to resolve both the lithospheric and deeper mantle structure. Slow velocities are widesp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
48
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 70 publications
14
48
0
2
Order By: Relevance
“…This kind of division is in good agreement with previous studies of subsurface structures that used other methodologies (e.g., Obrebski et al, 2012). For the areas having substantially thicker lithospheric roots (>200 km), such as the Ordos and the Yangtze cratons (grey outlines in Fig.…”
Section: Contributions From the Lithosphere And/or Asthenospheresupporting
confidence: 80%
See 1 more Smart Citation
“…This kind of division is in good agreement with previous studies of subsurface structures that used other methodologies (e.g., Obrebski et al, 2012). For the areas having substantially thicker lithospheric roots (>200 km), such as the Ordos and the Yangtze cratons (grey outlines in Fig.…”
Section: Contributions From the Lithosphere And/or Asthenospheresupporting
confidence: 80%
“…Tomography models show that the lithosphere in this area is relatively thin, with an average thickness of b 100 km (Obrebski et al, 2012;Zhao et al, in press). These lines of evidence suggest that velocity anomalies reflect features in the asthenosphere.…”
Section: Contributions From the Lithosphere And/or Asthenospherementioning
confidence: 97%
“…Our model shows relative low velocity anomalies along and to the south of the Kunlun and high velocity anomalies in northeast (Figure ). To the first order, this observation is consistent with large‐scale tomography models in Tibet [ McNamara et al ., ; Liang and Song , ; Pei et al ., ; Huang and Zhao , ; Yang et al ., , Li and van der Hilst , ; Obrebski et al ., ] that generally imaged low velocity anomalies beneath the Songpan‐Ganzi Terrane with the Kunlun fault as the northern boundary, indicating a hot and deformable lithosphere.…”
Section: Discussionmentioning
confidence: 97%
“…The most interesting feature in the 3‐D model of NE Tibet is a local low velocity anomaly in the shallow upper mantle beneath the restraining bend of the Kunlun fault (Figures and c), where high topography and thick crust are observed (Figures , , and ). Is this anomaly a local feature or a simple extension of the anomaly beneath the Songpan‐Ganzi Terrane as imaged in large‐scale models [ Yang et al ., , Li and van der Hilst , ; Obrebski et al ., ]? We conducted additional resolution tests to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…1a; e.g., Charvet et al, 1996). Seismic tomography studies revealed near horizontal high-velocity anomalies within the mantle transition zone (MTZ) beneath eastern China and interpreted them as the stagnant ancient slabs (e.g., Huang and Zhao, 2006;Zhao et al, 2007;Li and van der Hilst, 2010;Zhao et al, 2011;Obrebski et al, 2012;Wei et al, 2012). Therefore, the current thermal state around the MTZ may be influenced at the locations in which the slab still interacts with the MTZ.…”
Section: Introductionmentioning
confidence: 97%